Detoxification of zearalenone and ochratoxin A by ozone and quality evaluation of ozonised corn. Issue 11 (1st November 2016) - Qi, Lijun; Li, Yulin; Luo, Xiaohu; Wang, Ren; Zheng, Ruihang; Wang, Li; Li, Yongfu; Yang, Dan; Fang, Wenmiao; Chen, Zhengxing
ABSTRACT: Zearalenone (ZEN) and ochratoxin A (OTA) are secondary toxic metabolites of fungi that can contaminate a wide range of food and feedstuff. In this study, the effects of ozone treatment on ZEN and OTA and the quality of ozonised corn are investigated. Ozone significantly affects ZEN and OTA solutions. ZEN was undetectable 5 s after being treated with 10 mg l –1 ozone. However, OTA was resistant to ozonation with a degradation rate of 65.4% after 120 s of treatment. Moreover, ZEN and OTA solutions were difficult to degrade after being dried by a nitrogen stream. Results showed that ozone effectively degraded ZEN and OTA in corn. The degradation rates of ZEN and OTA in corn increased with ozone concentration and treatment time. The degradation of ZEN and OTA at different ozone concentrations appropriately conformed to first-order kinetics with an R 2 value > 0.8749. Furthermore, under the same conditions, corn with increased moisture content (MC) (19.6%) was more sensitive to ozone than corn with a low MC (14.1%). When treated with 100 mg l –1 ozone for 180 min, ZEN and OTA in corn with 19.6% MC decreased by 90.7% and 70.7%, respectively. To evaluate the quality of ozonised corn, subsequent quality experiments were conducted using corn samples treated at different times with 100 mg l –1 ozone. The MC of corn decreased after ozone treatment. The whiteness and yellowness of the corn increased and decreased with increasing time, respectively. The fatty acid value of the corn increased significantly ( p ≤ 0.05) after 180 min of treatment. This study verified that ozone can effectively degrade ZEN and OTA in corn, but slightly affected corn quality.